RELATIONSHIP BETWEEN SELF CONFIDENCE, STUDENT PERCEPTION ABOUT MATHEMATICS AND PARENTS ATTENTION WITH THE RESULTS OF LEARNING MATHEMATICS STUDENTS OF CLASS X - Handian Tangguh Permadi; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2019)
Numerous factors influence a low grade in mathematics. Confidence, students' perceptions towards mathematics, and parents' attention are three factors that are suspected of having a relationship with students' grades in mathematics. This study aims to determine whether or not there is a positive and significant relation between confidence, students' perceptions towards mathematics, and parents' attention with the grade results of learning mathematics on the tenth-grade students of Department of Mechanical Engineering (TP) State Vocational High School (SMKN) 3 Yogyakarta in the academic year of 2016/2017. The population used in this research is all the tenth-grade students of Department of Machinery Engineering SMKN 3 Yogyakarta in the academic year of 2016/2017 that in total is 94 students and divided into three classes. The sampling class is done using a random sampling technique, which generates two classes; TP2 class as a research class and TP1 class as a trial class. The data collection technique is using a documentation method, interview, test method, and questionnaire method. The instrument test analyses used are validity test, reliability test, and distinguishing power test. The prerequisite analyses test used the normality test, independent test, and linearity test. The data analyses used are linear regression analysis and correlation analysis. The results of this study show that there is a positive and significant relationship between confidence, students' perceptions of mathematics, and parents' attention with the results of learning mathematics with linear regression equation and double correlation coefficient (R) as 0.696. Furthermore, obtained 8.478 and 2.96. So, . Relative donations (X1) 35.069%, (X2) 49.845% and (X3) 15,086% with coefficient of double determination as 0.696 and effective donations (X1) 17.011%, (X2) 24.178%, and (X3) 15.086%.